Perancagan Sistem Infomasi Administrasi Berbasis Web (Studi kasus: Fakultas Teknologi Informasi Universitas Flores) - Natalia Uba Mudamakin (Program Studi Sistem Informasi Universitas Atma Jaya Yogyakarta, 2021)
Abstract. The very rapid development of information technology has made various fields of human activity begin to take advantage of this information technology to help ease the activities carried out, one of which is providing information and processing data, as well as the education sector in managing its administration effectively and efficiently. The website, which is one of the most widely used internet technologies to facilitate administrative management because it can be accessed easily anywhere and anytime, through the use of web-based information systems, problems regarding data redundancies at faculty, cool archives, errors in the process of faculty financial payments are slow report generation can be overcome. In overcoming this problem, through designing a website-based administrative information system using the waterfall-based system development method, it is hoped that it can increase the effectiveness and efficiency of the performance of the program administration system. After the development of the system has been tested, the result is that the administration system can be operated by the information system study program to help the work process more efficiently and optimally.Keywords: Information System; Administrative management; Data flow; Data archive; WEB.